Tindakan Persona Non Grata Terhadap Pejabat Diplomatik Dalam Rangka Implementasi Hukum Diplomatik (Studi Persona Non Grata Pejabat Diplomatik Rusia Untuk PBB Oleh Negara Amerika Serikat) - Sari, Iing Maida; Deliana, Evi; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Persona non grata actions are common in diplomatic relations between twocountries. However, if the Persona non grata is carried out on diplomatic officials who arepermanent representatives of a member country of an International Organization, namely theUnited Nations, how do Diplomatic Laws see this matter and how Diplomatic Law regulatesthis. From the background of the problem, the formulation of the problem was born, namely,first. What is the perspective of Diplomatic Law on the Persona non grata action by theUnited States of America against the diplomatic officials of the Russian State for the UnitedNations? second, How is the Implementation of Diplomatic Law in the Persona non grataaction by the United States of America against the diplomatic officials of the State of Russiato the United Nations? to know the Implementation of Diplomatic Law in the Persona nongrata action by the United States of America against the Diplomatic Official of the State ofRussia for the United Nations.The type of research conducted can be classified as normative-juridical research inwhich this research is carried out on legal principles that are based on certain areas of legalgovernance, by first identifying legal principles that have been formulated in certain laws. Inthis study, the data sources used were secondary data with primary, secondary, and tertiarylegal materials carried out by means of library research.From the results of the study it was found that, first, the diplomatic legal perspectiveon the actions of Persona non grata carried out by the United States of America againstRussian diplomatic officials for the United Nations is an act that is contrary to DiplomaticLaw. Persona non grata actions carried out by the United States of America againstDiplomatic Officers who are permanent representatives of Russia to the United Nationsbased on Diplomatic Law cannot be justified unilaterally. There must be coordination andapproval from the United Nations. Secondly, the implementation of Diplomatic Law on casesof Persona non grata carried out by the United States of America against Russia's permanentrepresentatives to the United Nations has not been implemented. Because it is proven thatthis Persona non grata action should not be carried out unilaterally by the United States ofAmerica but this is still done by the United States of America. And many provisions containedin diplomatic law are not renewing Visas 5 permanent representatives of Russia to the Unitednations, and not resolving matters that are not desirable by the United States or theproblemsthat are relatedto either United Nations or member countries. As contained inArticle 20 and 21 Headquarter Agreements, namely by forming the United Nations Committeand forming other agreements agreed upon by the United States and the United Nations.